(untitled) (Fiep Bulletin - online, 2014)
The military career demands a minimum physical condition from your professionals, enough for the acting of specific military functions, demanding a healthy body composition, as well as, levels of strength appropriate. Therefore, the objective of that study was to verify the body composition and the levels of students’ of the Preparatory Nucleus of Officials of the Reserve (NPOR) strength of João Pessoa-PB. The sample was composed by 40 students of the NPOR, with ages between 19 and 22 years, of the which it was collected data of the variables manual and lumbar strength, Body Mass, Stature and 10 different skinfolds. The Body Mass Index (BMI) was calculated, Thin Body Mass, Suitable Body Mass, Need to Put on weight, Need of Weigh loss, Body Density and Percentile of Fat. For the treatment of the data was used descriptive statistics (SPSS 10.0). As principal results we found: the average of the individuals’ BMI was considered normal (22,37kg/m2), the percentile of fat obtained through the somátório of skinfolds it also presented normal results (14,77%); 85% of the body weightl refer to the thin body mass, however if we consider the value of Thin Body Mass Suitable, we noticed that the subject of the study are on average 10,42 kg below the weight, fact that also contemplated in the need of putting on weight; prevalence of the strength exists in larger degree in the first attempt, and the same decreases in relation to the number of measures, a measured them of larger strength manual they are in the right that reveals a prevalence of strength of this hand, however, the military ones would be classified as weak in relation to strength of manual press in the right and very weak in the left hand. It can be concluded that the body composition of the military appraised is normal, already in relation to the levels of strength the need of a special attention once the results are considered below the healthy zone.